2017
DOI: 10.1117/1.jbo.22.5.056004
|View full text |Cite
|
Sign up to set email alerts
|

Polarization gating based on Mueller matrices

Abstract: Abstract. We present mathematical formulae generalizing polarization gating techniques. Polarization gating refers to a collection of imaging methods based on the combination of different controlled polarization channels. In particular, we show how using the measured Mueller matrix of a sample, a widespread number of polarization gating configurations can be evaluated just from analytical expressions based on the Mueller matrix coefficients. We also show the interest of controlling the helicity of the states o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Therefore, we can assume that the diattenuation effects of the sample are negligible, and the diattenuation information is not useful to improve the image contrast in this case. This result is in agreement with other studies in the literature , where most polarimetric analyses dealing with biological tissues focusses on retardance and depolarization.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, we can assume that the diattenuation effects of the sample are negligible, and the diattenuation information is not useful to improve the image contrast in this case. This result is in agreement with other studies in the literature , where most polarimetric analyses dealing with biological tissues focusses on retardance and depolarization.…”
Section: Resultssupporting
confidence: 93%
“…Different polarimetric studies of biological samples have shown that retardance and depolarization are the main polarimetric channels providing significant information of tissues . In addition, the information of samples encoded in the polarization of light strongly depends on the particular structure to be analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, MM measurements, combined with certain associated analytical tools (mainly, MM decompositions), not only allow an enhancement of the image contrast of biological samples, but also permit a physical characterization of the studied samples and the observation of new structures. Although we can define two groups, PGs have been recently linked with MM methods, showing that PG can be generalized as particular cases of a discrete combination of MM coefficients [13].…”
Section: Introductionmentioning
confidence: 99%